ABA Suppresses Botrytis cinerea Elicited NO Production in Tomato to Influence H2O2 Generation and Increase Host Susceptibility - Sivakumaran, Anushen; Akinyemi, Aderemi; Mandon, Julian; Cristescu, Simona M.; Hall, Michael A.; Harren, Frans J. M.; Mur, Luis A. J. (Frontiers in Plant Science, 2016)
Abscisic acid (ABA) production has emerged a susceptibility factor in plant-pathogen interactions. This work examined the interaction of ABA with NO in tomato following challenge with the ABA-synthesising pathogen, Botrytis cinerea. Trace gas detection using a quantum cascade laser detected NO production within minutes of challenge with B. cinerea whilst photoacoustic laser detection detected ethylene production – an established mediator of defence against this pathogen - occurring after 6 h. Application of the NO generation inhibitor N-Nitro-L-arginine methyl ester (L-NAME) suppressed both NO and ethylene production and resistance against B. cinerea. The tomato mutant sitiens fails to accumulate ABA (abscisic acid), shows increased resistance to B. cinerea and we noted exhibited elevated NO and ethylene production. Exogenous application of L-NAME or ABA reduced NO production in sitiens and reduced resistance to B. cinerea. Increased resistance to B. cinerea in sitiens have previously been linked to increased reactive oxygen species (ROS) generation but this was reduced in both L-NAME and ABA treated sitiens. Taken together, our data suggests that ABA can decreases resistance to B. cinerea via reduction of NO production which also suppresses both ROS and ethylene production.